Pengaruh work-life balance dan job involvement terhadap in-role performance dengan affective commitment sebagai variabel mediasi - Azizah, Alvi Nur; Rozaq, Khoirur (Universitas Negeri Surabaya, 2024)
The objective of this study is to gain a comprehensive understanding of how work-life balance, job involvement, and affective commitment contribute to enhancing in-role performance. It also examines the role of affective commitment in leveraging work-life balance to improve in-role performance and maximising job involvement to enhance in-role performance. This quantitative research, categorised as explanatory, employs the Structural Equation Model (SEM) method. The findings reveal that at PT. X, work-life balance does not directly influence in-role performance but has a positive and significant impact on affective commitment. This indicates that employees with a higher perceived work-life balance exhibit more outstanding affective commitment. Job involvement is shown to positively and significantly affect in-role performance and affective commitment, suggesting that higher job involvement enhances employee performance and commitment. Affective commitment significantly improves in-role performance, demonstrating its direct influence on employee performance. However, work-life balance does not significantly impact in-role performance through affective commitment as an intervening variable, as its indirect effect is less substantial than the direct effect. Conversely, job involvement significantly enhances in-role performance through affective commitment, indicating that affective commitment mediates the relationship between job involvement and in-role performance. This study's scope is limited to a single company. Hence, future research should encompass multiple companies for a larger sample size. Furthermore, future studies are recommended to explore in-role performance incorporating other variables such as leadership style or self-efficacy.